Odpowiedzi

Najlepsza Odpowiedź!
2009-12-02T19:21:29+01:00

d) 4x - 5y = -4
-2x + 3y = 1,1 |*2

4x-5y=-4
-4x+6y=2,2

y=-1,8

4x-5y=-4
4x+9=4 |-9

4x=-5
x=1,25

e) -2x + y = 0 |*3
3x - 3y =1

-6x+3y=0
3x-3y=1

3x=1
x=1/3

-2x+y=0
-2/3+y=0 |+2/3

y=2/3

f) 3x - 2y = -12 |*(-2)
2x - 5y = - 19 |*3

-6x+4y=24
6x-15y=-57

-11y=-33
y=3

3x-2y=-12
3x-6=-12

3x=-6
x=-2
2009-12-02T19:24:32+01:00
D)

4x - 5y = -4
-2x + 3y = 1,1 / *2

4x - 5y = -4
-4x + 6 y = 2,2
____________
y = -1,8

4x - 5* (-1,8) = -4
4x - (-9) = -4
4x + 9 = -4
4x = -4 - 9
4x = -13/ :4

x = - 3,25


e)

-2x + y = 0 / *3
3x - 3y =1

-6x +3y = 0
3x - 3y =1
____________
-3x = 1 / : (-3)
x = -1/3

3* (-1/3) - 3y = 1
-1 - 3y = 1
-3y = 2 / : (-3)
y = - 2/3

f)

3x - 2y = -12 / * (- 2)
2x - 5y = - 19 / *3

-6x + 4y = 24
6x - 15y = -57
_____________
-11y = -33/ : (-11)
y = 3

3x - 2*3 = -12
3x - 6 = -12
3x = -6 / :3
x = -2